0956 Trajectories of Poor Sleep Quality from Late Pregnancy to 3 Years Postpartum and Association with maternal Mood Disturbances: A Longitudinal and Prospective Cohort Study. (27th April 2018) - Wang, G; Deng, Y; Jiang, Y; Lin, Q; Zhu, L; Jiang, F
Abstract: Introduction: Women in pregnancy and postpartum periods have high rates of sleep problems that are associated with a wide range of detrimental mother and child outcomes, particularly postpartum depression and anxiety. However, no study has examined long-term trajectories of poor sleep quality from late pregnancy to early motherhood, and association with maternal mood disturbances. Methods: A longitudinal, prospective cohort study of 262 non-clinical women were at late pregnancy, 42 days, 3, 6, 9, 12, 18, 24, 36 months postpartum. Primary measures included the Pittsburgh sleep quality Index, the center for epidemiologic studies-depression scale, and the state-trait anxiety inventory. Group-based trajectory models was used to identify the distinguished sleep trend of these women. Results: Rate of poor sleep quality took a "U" shaped change, with a peak at 42 days postpartum (around 75%), remaining at equivalent level until 9 month postpartum compared to late pregnancy (around 45%), and fluctuating around 35% until 3 years postpartum. Three trajectories that can distinguish latent group variances in long-term change of sleep quality were identified, namely the stable-low complainants (29.4%), the decreasing-mild complainants (56.5%), and the stable-high complainants (14.1%). Poor sleep quality at late pregnancy held consistently higher risk of poor sleep quality at all postpartum following-up points. After controlling for covariants, the trajectory groups of poorer sleep quality demonstrated increased mood disturbances at 3 years postpartum. Replicating the analysis only in women without baseline symptoms of depression and anxiety above clinical cut-offs obtained similar results. Conclusion: Women are persistently subject to poor sleep quality from late pregnancy tp early motherhood, but follow distinct trajectories. Poor sleep quality and symptoms of depression and anxiety at late pregnancy can be used as early identifiers to the sleep trajectories. Trajectory of poor sleep quality inform severity level of mood disturbances in 3 years postpartum. Support (If Any): Chinese National Natural Science Foundation(81422040); MOE New Century Excellent Talents(NCET-13–0362); Ministry of Science and Technology(2016YFC1305203); Shanghai Science and Technology Commission(17XD1402800, 14441904004); Shanghai Jiao Tong University(YG2016ZD04).